2017
DOI: 10.4067/s0718-58392017000400303
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between grain quality of foxtail millet ( Setaria italica [L.] P. Beauv.) and environmental factors on multivariate statistical analysis

Abstract: Correlation between grain quality of foxtail millet (Setaria italica [L.] P. Beauv.) and environmental factors on multivariate statistical analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…The ADV ranged from 1.17 to 4.60, and Yuci had the highest ADV, which was significantly higher than that of Zezhou, Dingxiang, and Xingxian. Ning et al [21] found a lower ADV of millet grown in Yuci than was found in this study, likely due to differences in characteristics and interannual environments. The GC of crops determines whether they are soft or firm when cooked [36].…”
Section: Culinary Qualitycontrasting
confidence: 73%
See 3 more Smart Citations
“…The ADV ranged from 1.17 to 4.60, and Yuci had the highest ADV, which was significantly higher than that of Zezhou, Dingxiang, and Xingxian. Ning et al [21] found a lower ADV of millet grown in Yuci than was found in this study, likely due to differences in characteristics and interannual environments. The GC of crops determines whether they are soft or firm when cooked [36].…”
Section: Culinary Qualitycontrasting
confidence: 73%
“…The alkali digestion value (ADV) was determined according to the method described by Ning et al [ 21 ]. Twenty shelled foxtail millet grains of uniform size were placed in a Petri dish, and 10 mL of 1.7% KOH was pipetted into the dish until the grains were completely submerged.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Peng (2017) used grey incidence analysis to study the degree of incidence between meteorological disasters and grain yield per unit area and 5 specific grain crops in Henan Province from the perspective of light, moderate and severe disasters. Ning et al (2017) measured the degree of grey incidence between comprehensive quality of millet and environmental factors in 5 representative locations in Shanxi Province under different ecological conditions. Zhao et al (2017b) analyzed the spatio-temporal variation characteristics of degree of incidence between winter wheat yield at county level and climatic factors in the growth period of winter wheat.…”
Section: Literature Review Of the Application On Grey Model Technolog...mentioning
confidence: 99%